Transformasi Lahan Bekas Tambang Menjadi Lanskap Wisata Berbasis Masyarakat dan Ketahanan Pangan di Desa Lubuk Alung - Roni Vichaldry; Sinta Aulia; Jamilah; Osronita (Jurnal Ragam Pengabdian, 2026)
The former mining site in Lubuk Alung Village, Padang Pariaman Regency, West Sumatra, covering 7 hectares, presents significant environmental degradation characterized by water-logged pits, absence of topsoil, and sparse shrub vegetation. This study employed qualitative descriptive analysis conducted from September to November 2020, utilizing direct field observations, stakeholder interviews with six community members, village officials, and the Provincial Environmental Agency, supplemented by spatial data analysis including topographic maps, aerial photography, digital elevation models, and climatological data. The landscape design approach followed Gold's systematic planning process encompassing preparation, inventory, analysis, synthesis, conceptualization, and design phases. The recovery plan integrates nature-based solutions optimizing wetland-specific flora and fauna, creating a multifunctional landscape divided into buffer zones, cultivation areas, agricultural plots, development zones, and wetland-outbound tourism spaces. The design incorporates community-based tourism concepts featuring fish farming, agriculture, culinary experiences, West Sumatran handicrafts, and wetland recreational activities, supported by facilities including floating fish cages, agricultural demonstration plots, traditional pavilions, viewing decks, and outbound installations. The circulation system combines linear and radial pedestrian pathways using gravel and paving blocks, connecting key activity nodes. Conclusion: This landscape restoration framework demonstrates how degraded mining land can be transformed into productive, ecologically sound, and economically beneficial community assets, contributing to environmental conservation, food security enhancement through integrated aquaculture-agriculture systems, and local economic empowerment through participatory tourism management.